Endoscopic radiofrequency ablation for malignant biliary obstruction - Jarosova, Jana; Macinga, Peter; Hujova, Alzbeta; Kral, Jan; Urban, Ondrej; Spicak, Julius; Hucl, Tomas (World journal of gastrointestinal oncology, 2021)
Cholangiocarcinoma and pancreatic cancer are the most common causes of malignant biliary obstruction. The majority of patients are diagnosed at a late stage when surgical resection is rarely possible. In these cases, palliative chemotherapy and radiotherapy provide only limited benefit and are associated with poor survival. Radiofrequency ablation (RFA) is a procedure for locoregional control of tumours, whereby a high-frequency alternating current turned into thermal energy causes coagulative necrosis of the tissue surrounding the catheter. The subsequent release of debris and tumour antigens by necrotic cells can stimulate local and systemic immunity. The development of endoluminal RFA catheters has led to the emergence of endoscopically delivered RFA, a treatment mainly used for malignant biliary strictures to prolong survival and/or stent patency. Other indications include recanalisation of occluded biliary stents and treatment of intraductal ampullary adenoma or benign biliary strictures. This article presents a comprehensive review of endobiliary RFA, mainly focusing on its use in patients with malignant biliary obstruction. The available data suggest that biliary RFA may be a promising modality, having positive impacts on survival and stent patency and boasting a reasonable safety profile. However, further studies with better characterised and stratified patient populations are needed before the method becomes accepted within routine clinical practice.
Keywords: Biliary; Cholangiocarcinoma; Pancreatic cancer; Stenosis; Radiofrequency; Ablation